2020
DOI: 10.1371/journal.pone.0239724
|View full text |Cite
|
Sign up to set email alerts
|

First stage progression in women with spontaneous onset of labor: A large population-based cohort study

Abstract: To describe the duration, progression and patterns of first stage of labor among Swedish women. Design Population-based cohort study. Population Data from Stockholm-Gotland Obstetric Cohort 2008-2014 including ¼ of all births in Sweden, the final sample involved a total of 85,408 women with term, singleton, vertex, live fetuses experiencing spontaneous labor onset and vaginal delivery with normal neonatal outcomes. Main outcome measures Time to progress during first stage of labor using three approaches: 1) Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 46 publications
7
34
0
Order By: Relevance
“…Women admitted to the delivery hospitals between 2008 and 2014 in the region who met the described definition were deemed in the active first stage of labour and managed accordingly. The baseline characteristics for both study population and the target population, Supplementary Table S5 , comparable to the previous study by Lundborg et al 1 , showed that the subgroup of women in this study was equivalent to the population at large in terms of key characteristics. Further, this study cohort is based on a population with a large proportion of spontaneous vaginal births which is of importance when evaluating first stage duration and progression.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Women admitted to the delivery hospitals between 2008 and 2014 in the region who met the described definition were deemed in the active first stage of labour and managed accordingly. The baseline characteristics for both study population and the target population, Supplementary Table S5 , comparable to the previous study by Lundborg et al 1 , showed that the subgroup of women in this study was equivalent to the population at large in terms of key characteristics. Further, this study cohort is based on a population with a large proportion of spontaneous vaginal births which is of importance when evaluating first stage duration and progression.…”
Section: Discussionsupporting
confidence: 80%
“…Duration of labour varies between and within populations 1 3 . Determining normal and abnormal labour duration is complex because duration is influenced by multiple factors, such as: spontaneous or induced start of labour 4 , 5 , parity 2 , obstetrical management 6 9 , infant and maternal anthropometrics such as body mass index (BMI) and maternal age 10 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Women admitted to the delivery hospitals between 2008 and 2014 in the region who met the described definition were deemed in the active first stage of labour and managed accordingly. The baseline characteristics for both study population and the targetsubpopulation , Supplementary Table 6, comparable to the previous study by Lundborg, et al 1 , showed that the subgroup of women in this study was equivalent to the population at large in terms of key characteristics. Further, this study cohort is based on a population with a large proportion of spontaneous vaginal births which is of importance when evaluating first stage duration and progression.…”
Section: Strengths and Limitationssupporting
confidence: 86%
“…Duration of labour varies between and within populations [1][2][3] . Determining normal and abnormal labour duration is complex because duration is influenced by multiple factors, such as: spontaneous or induced start of labour 4,5 , parity 2 , obstetrical management [6][7][8][9] , infant and maternal anthropometrics such as body mass index (BMI) and maternal age [10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…76,77 A recent labor progress research from Sweden showed, in line with the studies by Zhang and Oladapo, an acceleration of cervical dilation at 5-6 cm; however, the median time in the first stage of labor was faster. 78 A large Norwegian study comparing labor outcomes in nulliparous women with spontaneous onset of labor managed according to either the partogram based on Friedman´s data or based on Zhang´s findings did not find any differences in adverse outcomes, including CS rate. 79 Overweight and obese women seem to have a slower first stage, but not second stage, of labor compared with normal weight women.…”
Section: Normal Progress Of Labormentioning
confidence: 92%